Early onset pre-eclampsia with severe features necessitating fetal delivery: outcome of pregnancies with birthweight 1000-1800g at Tygerberg Hospital 2017 - Adlam, Jan Andries (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2021.